2014
DOI: 10.1007/s12663-014-0698-5
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Maxillofacial Trauma Outcomes Based on a Survey of 65 Patients: A Prospective Study of Etiology, Incidence and Methods of Treatment

Abstract: Background The purpose of this study was to assess the etiology, incidence, and various methods of treatment of maxillofacial injuries in children presenting at our centre and to compare our findings with literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…In spite of that MVA is the most common cause of trauma in both adults and children, fall was the cause in 17.5% of the pediatric group and was not reported as a cause in the adult group (Table 1). Near results were also detected by Atilgan et al [16] and Arvind et al [13], while Jung et al [17] and Bharadwaj [18] found that fall was the most common cause.…”
Section: Discussionmentioning
confidence: 54%
“…In spite of that MVA is the most common cause of trauma in both adults and children, fall was the cause in 17.5% of the pediatric group and was not reported as a cause in the adult group (Table 1). Near results were also detected by Atilgan et al [16] and Arvind et al [13], while Jung et al [17] and Bharadwaj [18] found that fall was the most common cause.…”
Section: Discussionmentioning
confidence: 54%
“…(Youssef et al, 2018;Imahara et al, 2008;Vyas et al, 2008) Pacientes com essas fraturas, muitas vezes requerem acompanhamento cuidadoso para futuras deformidades faciais secundárias a lesões do centro de crescimento, particularmente do septo nasal e côndilo mandibular e outros déficits de longo prazo (Bhardwaj e Kumar, 2015). Portanto, quando indicado o tratamento cirurgico de fraturas faciais pediatricas, este deve ser feito de maneira adequada e oportuna, a fim de evitar consequências no crescimento e desenvolvimento da criança (Bhardwaj & Kumar, 2015;Youssef et al, 2018).…”
Section: Discussionunclassified
“…In the studies analyzed, mean age was 10.2 years, demonstrating a greater occurrence of facial trauma in adolescence, as reported previously ( 23 , 24 ). This type of trauma generally occurs as a child becomes more independent from family life and has greater contact with contact sports, urban violence or physical aggression at school or on the street ( 2 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%